Comprehending Antisemitism through the Ages: A Historical Perspective - Lange, Armin; Mayerhofer, Kerstin; Porat, Dina; Schiffman, Lawrence H. (An End to Antisemitism!, 2021)
The five volumes provide a compendium of the history of and discourse about antisemitism - both as a unique cultural and religious category. Antisemitic stereotypes function as religious symbols that express and transmit a belief system of Jew-hatred, which are stored in the cultural and religious memories of the Western and Muslim worlds. This volume explores the phenomenon in a historical perspective.